2014
DOI: 10.1021/om501142k
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of N2P2 Four-Membered Rings and the Effect of Their Ligand Coordination to M(CO)5 (Cr, Mo, and W)

Abstract: In this article the biradicaloid character of the ground-state structures of N2P2R2 (R = CH3) rings is studied using the DFT and CASSCF methods, and a satisfactory agreement of the B3LYP functional and CASSCF(6,6) ab initio method has been found. In order to obtain an adequate description of the biradicaloid character, we have combined two criteria: (i) singlet–triplet energy gaps and (ii) relative values of the occupation numbers for bonding and antibonding orbitals associated with the radical sites. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Furthermore, a natural bond orbital (NBO) analysis confirmed that there is still one lone pair on each phosphorus atom, but the σ 3 ‐P I center (natural population analysis (NPA) charge: +0.398) is more electron rich than the noncoordinated phosphorus center (NPA charge: +0.487), which makes it plausible that in every case the second Lewis acidic moiety is coordinated to the same P atom as the first. Related gold complexes of biradicaloid III (Scheme ) have been reported recently by Schulz et al., and group 6 complexes have been studied computationally by Frontera and Streubel . Similarly, when 1 b was treated with two equivalents of Cu I Cl, ( IPr ) 2 C 2 PP(CuCl) 2 ( 9 ) was isolated as a dark red solid.…”
Section: Resultsmentioning
confidence: 90%
“…Furthermore, a natural bond orbital (NBO) analysis confirmed that there is still one lone pair on each phosphorus atom, but the σ 3 ‐P I center (natural population analysis (NPA) charge: +0.398) is more electron rich than the noncoordinated phosphorus center (NPA charge: +0.487), which makes it plausible that in every case the second Lewis acidic moiety is coordinated to the same P atom as the first. Related gold complexes of biradicaloid III (Scheme ) have been reported recently by Schulz et al., and group 6 complexes have been studied computationally by Frontera and Streubel . Similarly, when 1 b was treated with two equivalents of Cu I Cl, ( IPr ) 2 C 2 PP(CuCl) 2 ( 9 ) was isolated as a dark red solid.…”
Section: Resultsmentioning
confidence: 90%
“…3 To date, several examples of stable cyclic singlet biradicaloids have been known, which recently were parts of excellent reviews by F. Breher, M. Abe, and Rivard et al [4][5][6] The chemistry of singlet biradicaloids is rich and was investigated mainly in the examples of [ClC(m-PMes*)] 2 (Mes* = 2,4,6-tri(tertbutyl)phenyl) by the groups of Niecke [7][8][9][10] and Yoshifuji [11][12][13] and [ i Pr 2 P(m-B t Bu)] 2 by Bertrand et al [14][15][16] More recently, the activation of small molecules [17][18][19][20][21] and the one-electron oxidation 22 23 and several other small molecules like alkynes, alkenes, diazenes, azides, diazomethanes, isonitriles, nitriles, or nitrosotoluene. [24][25][26][27] It is noteworthy to mention that in a recent computational study by Streubel and Frontera et al, 28 several isomers of complexes of P 2 N 2 singlet biradicaloids were investigated, based on complexes which were experimentally obtained 29 by the group of Paine in the early 1980s as a result of the first attempt of the reduction of dichlorodiphosphadiazanes [ClP(m-NR)] 2 (R = e.g. t Bu).…”
mentioning
confidence: 99%
“…We were intrigued by this quite original reaction and decided to investigate some of its aspects by DFT calculations at the B3PW91/6-31+G­(d,p)-Lanl2dz (W) level . It must be stressed here that a theoretical study of a biradicaloid M­(CO) 5 complex has revealed a satisfactory agreement between the DFT and higher level CASSCF methods . The overall reaction combines a cyclization and a C–H insertion.…”
mentioning
confidence: 73%
“…6 It must be stressed here that a theoretical study of a biradicaloid M(CO) 5 complex has revealed a satisfactory agreement between the DFT and higher level CASSCF methods. 7 The overall reaction combines a cyclization and a C−H insertion. Since most of the cycloadditions of electrophilic terminal phosphinidene complexes with alkynes are run in boiling toluene, it is well established that these phosphinidene complexes are unable to activate the C−H bonds of toluene.…”
mentioning
confidence: 99%